(3JjSjQ GdHjGf aj CMcGe GdbQBfs - (3LeGd GdOjf eMeO Hf Ydj Hf YHO Gddg GdehRYj Gdjefj, GHf fhQ GdOjfs
(3ChdgG (B:s
(3bGd Gdabjg YQa HGHf fhQ GdOjf GdehRYi Gdjefi GdMeO ddg GdPi Ndb GdEfSGf hYdeI GdbQBf hageg GdHjGf hQRbg Gdage hGdYQaGf s
(3BNQgG (B:s
(3hgPG eG fTQ Gddg GdcQje JYdjbI ef BjGJ GdCMcGe hEf cGf bO Hbi ai GdbQBf GdeLjO BjGJ cKjQI JJYdb HGdCMcGe s
(3GdfSNI HgG MhGTs
(3GdfSNI ecedI HNW MOjK hhQb MOjK HebOGQ (B23 (3hQbIs
(3hHHYV gGeTgG JYdjbGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs